Moral parenthood: not gestational - Lange, Benjamin (Journal of medical ethics, 2025)
Parenting our biological children is a centrally important matter, but how, if it all, can it be justified? According to a contemporary influential line of thinking, the acquisition by parents of a moral right to parent their biological children should be grounded by appeal to the value of the intimate emotional relationship that gestation facilitates between a newborn and a gestational procreator. I evaluate two arguments in defence of this proposal and argue that both are unconvincing.